SWOT ANALYSIS; THE TOOL OF ORGANIZATIONS STABILITY (KFC) AS A CASE STUDY - Omer, Soran Kakarash (Journal of process management and new technologies, 2018)
The project is an effort to test the role of SWOT analysis as a marketing implementation strategy to provide stable condition for organizations. In more detail SWOT analysis is independent variable and organization stability is dependent variable. The methodologies depend on the several problems by reviewing books and journals, as well as tracking down the information the KFC (Kentucky fried chicken) as a global brand and chain food. The result shows that accurate information which is obtained to managers through the analyzing and classifying with the application of SWOT and PEST has the importance role to make strategic plan and stable the organization for a longer time. To conclude, these strategies are playing and leading the essential role the organizations to conduct the best or at least optimal solutions with time and location respectively.